Examining Self-Efficacy as a Mediating Factor in Urban Generation Z's Agripreneurial Interest - Dessy Iriani Putri; Lorenta In Haryanto; Rizki Adi Puspita Sari (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
This research investigates how the university environment, income expectations, family environment, and role models influence agripreneurial interest among urban Generation Z, with self-efficacy examined as a mediating variable. A quantitative research design was adopted, and data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach, based on data from 88 Generation Z respondents in the JABODETABEK region. The findings reveal that self-efficacy, income expectations, and the university environment exert a significant direct influence on agripreneurial interest, while family environment and role models do not. Furthermore, the university environment significantly influences agripreneurial interest indirectly through self-efficacy, whereas other variables do not show significant indirect effects. This study is among the limited empirical research investigating self-efficacy as a mediating mechanism shaping agripreneurial interest among urban Generation Z. It contributes theoretically by positioning self-efficacy as a key psychological mechanism that explains how the university environment shapes agripreneurial interest. This study contributes theoretically by identifying self-efficacy as a key mediating mechanism that explains how the university environment shapes agripreneurial interest among urban Generation Z. The novelty of this research lies in empirically positioning self-efficacy as a central explanatory variable in agripreneurship studies on farmer regeneration, an area underexplored in the existing literature.